The role of Internet Financial Reporting (IFR) in mediating manufacturing firm value on Indonesia Stock Exchange (IDX) - Khoirul Fuad; Nurlita Dwi Ariyani; Retno Tri Handayani (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - This research aimed to determine the role of Internet Financial Reporting application for manufacturing companies on Indonesia stock exchange in the increase of firm value both directly and indirectly.Method - This research used a purposive sampling method. The number of data collected was 95 company samples. This research employed SPSS 25 for testing the data.  Result - The results of this study indicated that Internet Financial Reporting can mediate the relationship between institutional ownership and profitability on firm value.Implication - Internet Financial Reporting application for companies today attracts investors to invest their capital to the companies because of the ease in getting the information needed at any time.Originality - This study used Internet Financial Reporting as mediation and source of the data year 2018.